Numerical investigation of a 3D inertance pulse tube refrigerator from design prospective. (March 2019) - Kumar, Pankaj; Gupta, A.K.; Sahoo, R.K.; Jena, D.P.
Highlights: The computational overhead is the actual reason which may stop many researchers to solve in 3D. In 3D analysis modelling the appropriate contact of components and meshing are to be analysed. The complexity is alleviated by implementing user define function in case of 3D simulation. The numerical error on introducing pressure wave needs to be analysed. Abstract: The Inertance Pulse Tube Refrigerator (IPTR) has been widely accepted in industrial applications for its efficiency and compact in size. The complex physics involved in IPTR has been observed adequately in numerical technique, however, till date the 3D analysis has not been appreciated for its high computational requirement and issues involved. The present research propose a novel numerical simulation of an IPTR from design and assembly point of view. Various issues involved in simulating an IPTR has been investigated in detail, moreover, the recommendations have been made for attaining the desired solution. IPTR as an assembly has been analyzed numerically by addressing the complexities involved in modelling, appropriate contact of components and optimal meshing. The complications involved in simulating compressor by opting dynamic meshing technique has been observed complicated in case of 3D simulation and has been mimicked by introducing an user defined function (UDF). Moreover, the difficulties arise in using inappropriate element type in meshing, which generate numerical singularity or negative volume error, has also been addressed minutely. Summarizing, the report carries a detailed investigation of an IPTR and may be considered as first of its own kind in addressing the corresponding issues in detail followed by recommendations to design any IPTR from industrial design and fabrication prospective.